Reaksi Pasar Modal Terhadap Pengumuman Pandemi Covid-19 dan Pengumuman PPKM Level 4 Pada Indeks LQ45 - Basyith, Abdul; Ningsih, Aliya; Hidayat, Randy (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
T This study aims to identify and analyze the impact of COVID-19 and the implementation of PPKM level-4 on abnormal returns and stock trading on the LQ-45 with 3 time periods, namely 5, 30 and 60 days before after the announcement. The analytical technique used is a different test independent samples. The results of this study are based on 3 time window periods showing the announcement of covid-19 does not show any difference in abnormal returns. The existence of PPKM level-4 indicates an influence on abnormal returns for all windows. The announcement of the presence of covid has an effect for a period of 30 and 60 days, but for 5 days, it does not affect trading volume activity. PPKM level-4 has no impact on trading volume activity for 30 days but does affect 5 and 60 days. Announcement of the existence of covid-19 without tightening activities does not affect abnormal returns and trading volume, but the fact of activity restrictions through PPKM level-4 affects abnormal returns